PERAN GURU PENGGERAK DALAM MENUMBUHKAN BUDAYA POSITIF DI SEKOLAH DASAR - Laila Rahmasari; Maryono; Khoirunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
One of the positive cultures in SDN 002/XI Pasar Sungai Penuh that must be developed by the driving teacher in carrying out his role is a positive culture of independent learning. This study aims to determine the role of the driving teacher in fostering a positive culture of learning independence at SD Negeri 002/XI Pasar Sungai Penuh. To find out the obstacles faced by the driving teacher in fostering a positive culture of learning independence at SD Negeri 002/XI Pasar Sungai Penuh. In this study, researchers used a qualitative approach with the type of research, namely case studies. This research was conducted at SD 002/XI Pasar Sungai Penuh. The subjects in this study were the Principal and the driving teacher. The data collection techniques used were interviews, observation and documentation. The data analysis technique used is through data reduction, data presentation and conclusion drawing. The results of this study indicate that 1) Teachers in SD 002/XI Pasar Sungai Penuh have a significant contribution in fostering a positive culture of learning independence. 2) To improve the effectiveness of the mobilising teachers' efforts, stronger and more equitable support from the whole school community, increased access to adequate resources, and a more flexible approach to curriculum implementation are needed. Based on the results of the research, it can be concluded that Master Teachers have an important role in fostering a positive culture of learning independence to improve the quality of education in schools and face a number of significant obstacles that need to be overcome.